WHEN LIFE AND JOB SKILLS MEET: TOWARDS A MODEL FOR THE DEVELOPMENT OF SPORTS SCIENCES STUDENTS' CAREER - Claudia MAULINI; Espedito LATERZA; Alessandra FAZIO; Mascia MIGLIORATI; Antonio SÁNCHEZ-PATO; Emanuele ISIDORI (Cluj University Press, 2022)
The development of soft skills and critical-reflexive skills for the design and implementation of sport activities that respond to the new challenges of the sport labour market is fundamental for the expert in Sport Sciences. The paper presents the results of the implementation of the ESLP project at the Foro Italico University in Rome, which aimed to develop the necessary soft skills for leadership in future experts in sport sciences. Received: 2022 February 22; Revised: 2022 March 20; Accepted: 2022 March 22; Available online: 2022 May 5; Available print: 2022 May 30.